The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/treephys/tpv127
|View full text |Cite
|
Sign up to set email alerts
|

Integrated physiological and hormonal profile of heat-induced thermotolerance inPinus radiata

Abstract: Despite great interest, not only from the economic point of view but also in terms of basic science, research on heat stress tolerance in conifers remains scarce. To fill this gap, a time-course experiment using expected temperature increase was performed aiming to identify physiological and biochemical traits that allow the characterization of heat-induced thermotolerance and recovery in Pinus radiata D. Don plants. Several physiological parameters were assessed during heat exposure and after recovery, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 61 publications
5
54
1
Order By: Relevance
“…A rapid proteomic heat-shock response that could be mimicked to some extent by cytokinin treatment at standard temperature has also been reported [136], indicating that cytokinin may play a role in temperature perception. Moreover, the accumulation of cytokinin has been observed in Pinus radiata under prolonged heat stress and in recovered plants [137,138]. Plants with increased levels of cytokinins show a higher accumulation of heat-shock proteins [107,139,140] and enhanced activity of the antioxidant system [88,112].…”
Section: Temperature and Cytokininmentioning
confidence: 99%
“…A rapid proteomic heat-shock response that could be mimicked to some extent by cytokinin treatment at standard temperature has also been reported [136], indicating that cytokinin may play a role in temperature perception. Moreover, the accumulation of cytokinin has been observed in Pinus radiata under prolonged heat stress and in recovered plants [137,138]. Plants with increased levels of cytokinins show a higher accumulation of heat-shock proteins [107,139,140] and enhanced activity of the antioxidant system [88,112].…”
Section: Temperature and Cytokininmentioning
confidence: 99%
“…Escandón et al. (2016) also found that soluble sugars seemed more closely associated with plant responses to increasing number of days exposed to heat stress, although they did not measure starch. Interestingly, glucose + fructose was not significantly affected by day or treatment in the 45‐ and 90‐min groups (Figure 6), consistent with Lafta and Lorenzen (1995) that found no effect of temperature on sugar levels in potato and attributed this to coordinated control of sugar metabolism in response to high temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of damage as measured with photosynthesis at day 2 did not differ between leaf age classes nor treatment, suggesting that leaf age may influence the capacity to recover more than the extent of damage incurred, although both characteristics influence the ability to withstand heat stress (Escandón et al., 2016). Consistent with our second hypothesis, the 90‐min duration of heat stress resulted in both greater physiological damage and slower recovery than the 45‐min group as measured with F V / F M and slower recovery as measured with photosynthesis (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of moderate heat stress on the leaf proteomes of P. euphratica plantlets in hydroponic culture were reported 10 years ago (Ferreira et al ., ) and, very recently, other authors have replicated some aspects of this experiment with Pi. radiata , but with a much diversified and interesting analytical test (Escandón et al ., ). Although Pi.…”
Section: Contribution Of the Mep Pathway At High Temperaturementioning
confidence: 97%
“…Therefore, its accumulation is not strictly dependent on VIO; instead, VIO abundance is dependent on ZEA conversion, but, as VDE activity is increased by electrolyte leakage at high temperature, the ZEA pool increases, whereas the VIO pool decreases, leaving less VIO to be ultimately converted into ABA. However, ABA and SA biosynthesis have been found to increase at high temperature in Pinus radiata (Escandón et al ., ), and moderate heat stress has been found to have a positive impact on net photosynthesis and growth. So, how are the xanthophyll cycle, ABA and SA related in acclimation to high temperature?…”
Section: Redox Poise and Photophosphorylation Reactionsmentioning
confidence: 99%